Linguistic Means of Constructing “Own” and “Other” in B. Akunin’s Novel "The Diamond Chariot" - Sahverdova, Nava-Vanda; Urazbekova, Alina (Slavica, 2022)
The article discusses the ways of linguistic construction of the concepts of “own” and “other” in B. Akunin’s novel The Diamond Chariot. The methodological basis of the study is cognitive discursive analysis. The protagonist of the novel arrives in Japan and meets with new realities, objects, places, social organization of life. In this process, we observe the contact of two cultures – the Japanese and European-Russian. Japanese appears in the novel in a wide layer of Japanese vocabulary, which is introduced into the text in a variety of ways (translation in the text, translation in a footnote, explanation, repetition with translation, the use of a foreign word in a typical context).The process of cognition of a foreign culture is accompanied by constant assessments through the prism of one’s, previously learned experience. Evaluation is a structural characteristic of the construction of one’s “own” and “others’” and reflects the dynamic nature of the process of acquaintance with a foreign culture. Other way stoembed foreign words in the text – using the structure of the concept – are also presented in the article. The experience of the meeting of two cultures also appears in the linguistic form in the communication of multilingual heroes of the novel among themselves, the characteristics of this discourse of strangers are described (interspersed in English, as well as interspersed in English and Japanese, written in Cyrillic).